2020
DOI: 10.3390/cancers12102750
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Ductal Adenocarcinoma (PDAC) Organoids: The Shining Light at the End of the Tunnel for Drug Response Prediction and Personalized Medicine

Abstract: Pancreatic ductal adenocarcinoma (PDAC) represents 90% of pancreatic malignancies. In contrast to many other tumor entities, the prognosis of PDAC has not significantly improved during the past thirty years. Patients are often diagnosed too late, leading to an overall five-year survival rate below 10%. More dramatically, PDAC cases are on the rise and it is expected to become the second leading cause of death by cancer in western countries by 2030. Currently, the use of gemcitabine/nab-paclitaxel or FOLFIRINOX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 131 publications
0
35
0
Order By: Relevance
“…Interestingly, we found that fraxetin can enhance the sensitivity of PCCs to the chemotherapy drug gemcitabine. Gemcitabine is accepted as the standard treatment for patients with locally or metastatic advanced PDA, but the problem of its drug resistance has become increasingly prominent [39]. How to solve the weakening of its anti-tumor effect due to drug resistance is an important task now.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we found that fraxetin can enhance the sensitivity of PCCs to the chemotherapy drug gemcitabine. Gemcitabine is accepted as the standard treatment for patients with locally or metastatic advanced PDA, but the problem of its drug resistance has become increasingly prominent [39]. How to solve the weakening of its anti-tumor effect due to drug resistance is an important task now.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, most PDX models involve subcutaneous implantation of patient tumour tissue into immune-compromised mice which is a poor representation of the tumour microenvironment and low take rates can bias more aggressive disease [ 26 ]. Recently, organoids have gained much traction as a rapid and efficient model of interpatient heterogeneity with potential to guide functional precision medicine for PDAC [ 27 , 28 ].…”
Section: Pre-clinical Models In the Precision Medicine Pipelinementioning
confidence: 99%
“…Despite the many advantages of the tumour organoid model, many of the microenvironmental features discussed above are not recapitulated. Several studies have recently attempted to co-culture organoids with CAFs or immune cells, as reviewed recently [ 27 , 28 ], but the CAFs added to the organoids are not matched to the same patient and these co-culture systems also lack the presence of an ECM that matches human disease.…”
Section: Models That Reflect the Complex Microenvironment Are Required To Inform Functional Precision Medicine In Pdacmentioning
confidence: 99%
“…They showed PDOS drug screening with 100% sensitivity, 93% specificity, 88% positive predictive value, and 100% negative predictive value in forecasting response to targeted agents or chemotherapy in patients [ 16 ]. Several pilot studies on PDAC drug screening related to clinical data have been vigorously pursued based on this milestone study [ 56 , 62 , 77 ]. The report by Tiriac et al is currently the largest study of drug screening using PDOs [ 62 ].…”
Section: Personalized Cancer Treatment Using Pharmacological Profimentioning
confidence: 99%
“…In addition, Frappart et al also reported a drug screening study for 22 anticancer drugs in patients with PDAC [ 77 ]. In the representative cases presented in this study, the screening test result was clarified five days after the initial treatment of FORFIRINOX for metastatic PDAC.…”
Section: Personalized Cancer Treatment Using Pharmacological Profimentioning
confidence: 99%